(untitled) (Mongolian Journal of Agricultural Sciences, 2021)
This survey to comparative investigates on fat and fatty acid composition in muscles depends on season effects of pastoral and grain fed Mongolian breeds sheep (Mongolian grassland pastoral Mongolian sheep, Inner Mongolian grassland pastoral and grain fed Ujumqin sheep) muscle’s longissimus dorsi. Two breeds three kinds Mongolian sheep muscle’s longissimus dorsi IMF content and fatty acids were analyzed by gas chromatography after methyl esterification. The result reveals that: (1) The IMF content in pastoral of mongolian and Ujumqin sheep muscles was between winter and summer seasons observed extreme differences (p<0.01), but no extreme differences (p>0.01) in grain fed Ujumqin sheep. (2) The result showed that there were 29 identified fatty acids in the muscle’s longissimus dorsi means of winter season pastoral Mongolian, Ujumqin and grain fed Ujumqin sheep, where in the content of palmitic acid, stearic acid and oleic acid were 71.45%, 73.17%, 72.02% of the total content of fatty acids respectively. Also saturated fatty acids accounted for 44.49%, 46.27%, 45.37%; monounsaturated fatty acids accounted for 35.68%, 36.09%, 35.9; polyunsaturated fatty acids accounted for 8.18%, 8.33%, 9.32% respectively. In the summer muscle’s longissimus dorsi means of Mongolian, Ujumqin and grain fed Ujumqin sheep were 31, 31, 26 identified fatty acids, where in the content of palmitic acid, stearic acid and oleic acid were 75.96%, 77.17%, 72.79% of the total content of fatty acids respectively. Also saturated fatty acid accounted for 48.35%, 48.09%, 46.31; monounsaturated fatty acids accounted for 36.46%, 37.66%, 36.54; polyunsaturated fatty acids accounted for 7.07%, 7.43%, 8.05% respectively. Therefore, positive feature of pastoral Mongolian and Ujumqin sheep in muscle’s longissimus dorsi means that levels of the nutritionally important long chain PUFA EPA C20:5, DHA C22:6 was in winter 1.2-1.8%; in summer of the total content of fatty acids 1-1.2% respectively. But grain fed Ujumqin sheep muscle’s different parts means only identified long chain PUFA EPA C20:5 was in winter and summer 0.8% of the total content of fatty acids and lower than pastoral Mongolian and Ujumqin sheep 1%. Монгол хонины нурууны булчин махны тосны хүчлийн бүрдлийн судалгаа Энэхүү судалгаагаар өвөл болон зуны улирлын 2 үүлдэрийн 3 төрлийн Монгол хонины (Бэлчээрийн Монгол, Үзэмчин болон суурин маллагаатай Үзэмчин) нурууны булчин маханд (M. longissimus dorsi) тос болон тосны хүчлийн бүрдлийг харьцуулан судалсан болно. Дээрх 3 төрлийн хонины нурууны булчин эдийн тосыг ялган хэмжээг тогтоож, метил эфиржүүлсний дараа хийн хромотаграфаар тосны хүчлийн бүрэлдэхүүнийн тодорхойлсон. Булчин эдийн тосны агууламжийн үр дүн: Бэлчээрийн Монгол болон Үзэмчин хонины гуяны булчин эдийн тосны агууламж нь өвөл болон зуны улирлын хооронд хэт их утга (p<0.01) илэрсэн. Тосны хүчлийн бүрэлдэхүүний үр дүн: Өвлийн улирлын бэлчээрийн Монгол, Үзэмчин болон суурин маллагаатай Үзэмчин хонины longissimus dorsi булчин эдэд нийт тосны 89.35%, 91.19%, 90.6% -ийг 29 төрлийн тосны хүчил бүрдүүлж түүнээс пальмитины (C16:0), стеарины (C18:0), олеины хүчлүүд (C18:1) хүчлүүд 71.45%, 73.17%, 72.02%-ийг эзэлж байв. Зуны улиралд хонины нурууны булчин эдийн нийт тосны 91.88%, 93.18%, 90.9% -ийг 26-31 төрлийн тосны хүчил бүрдүүлж түүнээс пальмитины (C16:0), стеарины (C18:0), олеины хүчлүүд (C18:1) хүчлүүд 75.96%, 77.17%, 72.79%-ийг тус тус бүрдүүлж байна. Өвлийн улирлын бэлчээрийн Монгол, Үзэмчин болон суурин маллагаатай Үзэмчин хонины нурууны булчин эдийн дундаж ханасан тосны хүчил 44.49%, 46.27%, 45.37%’; мониен хүчил 35.68%, 36.09%, 35.9%; полиен хүчил 8.18%, 8.33%, 9.32%; Зуны улиралд ханасан хүчил 48.35%, 48.09%, 46.31%; мониен хүчил 36.46%, 37.66%, 36.54%; полиен хүчил 7.07%, 7.43%, 8.05% тус тус агуулагдаж байв. Эмчилгээний өндөр ач холбогдолтой гэгдээд байгаа EPA C20:5 болон DHA C22:6 олон холбоот тосны хүчлүүд бэлчээрийн Монгол болон Үзэмчин хонинд эдгээр хүчлийн нийлбэр өвлийн улирал 1.2-1.8%, зуны улиралд 1-1.2% агуулагдаж суурин маллагаатай Үзэмчин хонины нурууны булчин махнаас 1% орчим өндөр агуулагдаж байгаа бэлчээрийн хонины махны ач холбогдлыг илэрхийлэх үндэслэлтэй. Түлхүүр үг: Монгол хонь, Үзэмчин хонь, тосны хүчил, өвөл, зун